Emission Mössbauer study of CMR manganite La₀.₈Ca₀.₂MnO₃. II. Step-by-step snapshots of the metal-insulator transition - Chechersky, V.; Nomura, K.; Nath, A.; Ju, H.; Greene, R.L. (Физика низких температур, 1997)
We follow the step-by-step progression of events while approaching the Curie temperature Tc from below using ⁵⁷Co substituent as a microprobe in an emission Mössbauer study combined with resistivity measurements. In the temperature range 0.33<T/Tc ≤ 1, the material consists of a mixture of ferromagnetic and paramagnetic regions within the same matrix. An increase of the amount of paramagnetic fraction is accompanied by a decrease in electron delocalization in the ferromagnetic regions. At T≥Tc, the electrons are localized to neighboring Mn⁴⁺/Mn³⁺ pairs only, in about 46% of the paramagnetic species. The strength with which Mn atoms are bound to the neighbors also decreases progressively and rather steeply in the range 0.65<T/Tc=1. Zero field resistivity, ρ0, follows linearly with the amount of the paramagnetic phase in the range 0.65<T/Tc<1 and still shows metal-like behavior up to T/Tc≈1.03. Remove selected